Education in the French Outermost Regions : interculturation as a basis for a necessary work of memory? - Oulahal, Rachid (2022)
The French outermost regions are fully part of the European Union though they are geographically distanced from continental France. Moreover, these regions inscribe within France’s history though they also have their own history apart from France, a history grounded within their geographical surroundings but also a history between slavery and colonization. In 2022, education is still both a priority and an enigma for the French government when it comes to its outermost regions (Guadeloupe, Guyana, La Reunion, Martinique, Mayotte and Saint-Martin). Strong differences have been pointed out between these environments and metropolitan France regarding the education system and its efficiency. The main issue for the French government is indeed that the Outermost regions are different from metropolitan France but they are also very different from one to another. These various disparities make it difficult to think of a common school system and curriculum. The goal of this article is to provide an update on education issues France has to deal with regarding its outermost regions. We will then investigate how these issues can be related to memory matters, both individual and collective, and how an intercultural perspective can be regarded as a basis for a necessary work of memory towards a more appropriate educational system.